Twelfth Night / Text and Performance - Macmillan; Potter Lois (1985)
This volume in the ''Text and Performance'' series shows how Twelfth Night works as drama and how the text is realized through performance. Acknowledgements, General Editor's Preface, Plot Synopsis and Sources, Text, Introduction, Interpreting the Title, Patterns of Language and Action, Close Analysis: Act V - Scene i, A Play for Actors, Performance, Introduction, The Setting, Romance, Comedy, Reading List, Index of Names.